Plan de marketing para la empresa comercial don Alberto de la ciudad de Quevedo año 2015 - Pisco Laz, Katherine Lorena (2016)
Today's businesses are subject to constant changes that occur at the enterprise level, which is an obstacle to the institutions that have not achieved the objectives they arise and for this reason this research, entitled "Plan Marketing for the trading company Don Alberto Quevedo City "dedicated to the purchase and sale of consumer products has been developed with the purpose of giving a theoretical and technical support to the need administrator to generate greater influx of people and consumers. The main problem lies in the low trading volume of its sales for which it was established: An analysis of the situation of the company "Comercial Don Alberto" starting from the internal aspects as its background in the market, the products offered, and ending at the external aspects such as economics and politics; using tools such as survey and interview acknowledged and direct observation of its main activities, the market covers their geographic, demographic and description of the customer profile, highlighting its: 1) Strengths as it is their relative low price with competition and good location area 2) Weaknesses with the lack of positioning and lack of a good corporate image 3) Advanced Technology Opportunities SMEs 4) Threats such as strong competition and high taxes You can view a proposed marketing plan to achieve the positioning and improve the sales volume of the company Comercial Don Alberto located in the city of Quevedo with over 15 years experience but has not had much market share. market research on the tastes and preferences of consumers when choosing a shop to shop, one of the most important points in this research was conducted was the market share now occupied by the "Commercial Don Alberto" ( 4%) being an indicator to help to establish new goals and marketing strategies. And finally the control and monitoring variables that will determine the effectiveness of the plan with a financial aspect that will have an investment of $ 6,514.00 are identified.